Management of pulp canal obliteration using static-guided endodontic technique: Case series - Afzal Ali; Aasima Ishaq; Payal Jain; Sajid Ali (Wolters Kluwer Medknow Publications, 2022)
The present case series aims to describe the management of teeth with pulp canal obliteration (PCO) using the novel static-guided endodontic technique. Traumatic dental injury may result in partial or complete PCO, with and without periapical rarefaction and pose challenges during endodontic management. Three young adolescent patients presented to the department with a chief complaint of pain/discoloration/broken upper front teeth. The teeth were tender on percussion. Thermal and electrical pulp tests were negative for the concerned incisors. The periapical radiographic examinations revealed PCO and signs of periapical changes. A diagnosis of pulp necrosis; symptomatic apical periodontitis was established and nonsurgical endodontic treatment using the guided endodontic approach was planned with the patient consent. A cone-beam computed tomography (CBCT) scan and intraoral scanning were obtained using the special software to facilitate guided endodontics procedure. The surgical guides and a customized drill were fabricated. The drilling depth for the access to the calcified part was established using CBCT data, ensuring straight-line access. Conventional root canal treatment was completed. One-year follow-up examination revealed the absence of pain and periapical healing. In complicated cases with PCO and apical periodontitis, a CBCT and "Guided Endodontics" could be useful to save the tooth with minimal destruction of tooth structure and increase the chances of endodontic success.